Preharvest treatment of ‘Gala’ apples with 1-MCP and AVG – I: Effects on fruit maturation on the tree - Argenta L.C. (2018)
© 2018 International Society for Horticultural Science. All rights reserved.The study evaluated the efficacy of a sprayable formulation of 1-methylcyclopropene (1-MCP) to delay fruit maturation on the tree in comparison to aminoethoxyvinylglycine (AVG). 1-MCP (150 mg L-1) and AVG (124 mg L-1) were sprayed to ‘Imperial Gala’ and ‘Royal Gala’ apple trees from two commercial orchards, 7 and 28 days before commercial fruit harvest maturity, respectively, during four consecutive years. Untreated trees were used as control. Fruit were harvested weekly, during four weeks from the 7th day after 1-MCP spray and assessed one day after harvest. The extent of fruit maturation delay on the tree by 1-MCP and AVG was quantified by linear regression analysis of fruit firmness as a function of harvest date. The estimated date when apple fruit reached firmness of 71.1 N on the tree was delayed for 5.3 to 5.6 days by 1-MCP and for 9.0 to 9.4 days by AVG in comparison to the control, depending on cultivar-orchard. Indices of fruit maturity and quality at harvest were also estimated by linear regression analysis for the estimated date when fruit reach flesh firmness of 71.1 N on the tree. 1-MCP and/or AVG treated fruit had similar or lower ethylene production rates, starch index, titratable acidity and red color and similar or greener background color than control, at estimated harvest dates when fruit of all three treatments reached the same firmness of 71.1 N. 1-MCP and AVG treatments did not affect rates of fruit growth. However, at estimated dates when fruit of all treatments reached the firmness of 71.1, 1-MCP and AVG treated fruit were 2.1 to 7.1% larger than control fruit.